Who Ever Thought Need-Based Grants Would Increase Low-Income College Enrollment? - Hansen, W. Lee (My University, 2007)
When Congress established the Basic Education Opportunity Grant (BEOG) program in 1972, research predicted need-based grants would remove an important financial barrier to college attendance and raise college enrollment rates among young people from low-income families. However, a recent study suggests that the BEOG program and the later Pell grants failed to increase enrollment rates among low-income youth. In contrast, enrollments among young people in the top half of the family income distribution have climbed rapidly. Join W. Lee Hansen for a discussion of the possible reasons behind these counterintuitive results.
Keywords: Finance and Economics; Access, Persistence, and Success